Enhancing charge separation on high symmetry SrTiO3 exposed with anisotropic facets for photocatalytic water splitting. Issue 7 (21st June 2016) - Mu, Linchao; Zhao, Yue; Li, Ailong; Wang, Shengyang; Wang, Zhiliang; Yang, Jingxiu; Wang, Yi; Liu, Taifeng; Chen, Ruotian; Zhu, Jian; Fan, Fengtao; Li, Rengui; et al.
Abstract : Spatial charge separation achieved on the anisotropic facets of high symmetry SrTiO3 nanocrystals for highly efficient photocatalytic overall water splitting. Abstract : One of the challenging issues in photocatalytic overall water splitting is to efficiently separate the photogenerated charges and the reduction and oxidation catalytic sites on semiconductor-based photocatalysts. It has been reported that the photogenerated charge can be separated between different facets of a semiconductor crystal with low symmetry. However, many semiconductor crystals possess high symmetry (such as the cubic phase) and expose isotropic facets, which are not suitable for charge separation between the facets. Herein, using a nanocrystal morphology tailoring strategy, we synthesized the exposed facets of high symmetry SrTiO3 nanocrystals from isotropic facets (6-facet SrTiO3 ) to anisotropic facets (18-facet SrTiO3 ), which leads to the exposure of different crystal facets. We found that the reduction and oxidation catalytic sites can be separately distributed only on the anisotropic facets of 18-facet SrTiO3 nanocrystals, but randomly distributed on every facet of 6-facet SrTiO3 nanocrystals. Based on these findings, the selective distribution of dual-cocatalysts on the anisotropic facets of 18-facet SrTiO3 nanocrystals leads to a fivefold enhancement of apparent quantum efficiency. The superior performance can be attributed to the charge separation between anisotropic facets and the separation of the reduction and oxidation catalytic sites to reduce the charge recombination. These findings will be instructive for the rational design of a high efficiency photocatalytic system for solar energy conversion.